2021
DOI: 10.20944/preprints202102.0313.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Impact of New Ways of Working on Organizations and Employees: A Systematic Review of Literature

Abstract: A new research stream emerged in the 2000s dedicated to flexible work arrangements in public and private organizations, called “new ways of working” (NWW). This article aims to examine NWW from both a theoretical and empirical perspective, focusing on outcomes of this new concept and the debate between “mutual gains” vs. “conflicting outcomes.” Through a literature review, it examines this research field’s innovation and its rather vague the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
(88 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, future studies could extend the current research model by adding organizational outcomes such as business outcomes (Blok et al, 2012), organizational performance, innovation performance and competitive advantage. A recent systematic review revealed other organizational and employee factors that could be affected by NWW and could play a mediating or moderating role in the relationship between NWW and IWB (Renard et al, 2021). Moreover, the current study depended on self‐report measures for both NWW and IWB, which are not free of bias even if it was confirmed that the collected data were free of common method bias.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, future studies could extend the current research model by adding organizational outcomes such as business outcomes (Blok et al, 2012), organizational performance, innovation performance and competitive advantage. A recent systematic review revealed other organizational and employee factors that could be affected by NWW and could play a mediating or moderating role in the relationship between NWW and IWB (Renard et al, 2021). Moreover, the current study depended on self‐report measures for both NWW and IWB, which are not free of bias even if it was confirmed that the collected data were free of common method bias.…”
Section: Discussionmentioning
confidence: 99%
“…To do so, this study used the job demands-resources (JD-R) model, which assumes that the job characteristics, namely, job demands and job resources, are important predictors of employee outcomes, such as exhaustion, work engagement, or even perceived performance, in various occupational settings ( Bakker & Demerouti, 2017 ). So far, the empirical evidence regarding the effects of NWW on employee outcomes such as performance, work engagement, satisfaction and health, is mixed and no consensus exists on whether NWW practices have a positive impact on employees’ performance and well-being ( Renard et al, 2021 ). Moreover, to date, in the context of the COVID-19 crisis, there are no empirical data available to assess whether NWW practices exert an influence—positive or negative—on work engagement, work exhaustion, and self-perceived individual performance.…”
mentioning
confidence: 99%
“…Another reason for choosing single-item measurement approach in the study was that there is no theoretical or empirical consensus about the respective relevance and importance of different facets of knowledge work performance drivers. In general, theoretical understanding about the content of different constructs in a variety of approaches seeking to operationalize the New Ways of Working (as SmartWoW) are only emerging at the moment (Renard et al , 2021). It is more cautious to include wider array of facets, but with lighter measures to the study, than exclude prematurely and without firm evidence certain facets completely from the study.…”
Section: Methodsmentioning
confidence: 99%